Species Diversity of Bivalves and Gastropods at the Tanjung Rising Coastal, Bangka Belitung Island - Fatonah, Chintya Nurul; Ningtias, Restu Ayu; Pertiwi, Meilisha Putri; Rostikawati, Raden Teti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Tanjung Rising Coastal, located in Dendang Village, Bangka Belitung Islands, has a large variety of substrates and organisms. One of the types of marine life studied is the Mollusk Phylum including the Bivalve and Gastropod classes. To find out the diversity of Bivalvia and Gastropoda, this study was carried out on Tanjung Rising Coastal, Bangka Belitung Islands. The study was conducted in December 2020-August 2021, using belt transect method with purposive sampling technique. Samples were collected at station 1 with a sandy substrate and station 2 with a muddy substrate. The results of this study found 1,372 individuals from the Bivalvia class consisting of 7 families and 12 species, while from the Gastropod class yielded 2,630 individuals consisting of 5 families and 7 species. The diversity and evenness index at both stations is relatively low which means that there are species that dominate, because both stations have good habitats for the dominating species. In addition, temperature, pH, salinity, depth, and strong currents showed good values for Bivalvia and Gastropoda habitat. In summary, Tanjung Rising Beach is still a good habitat for invertebrate animals, especially Bivalvia and Gastropoda.